Energy Analysis of Small-Scale Ethanol Production from Cassava: A Case Study of the Cassakero Project in Nigeria - Ohimain, Elijah I. (Journal of Technology Innovations in Renewable Energy, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The Federal Government of Nigeria recently announced the replacement of kerosene household cooking fuel with ethanol produced from cassava feedstock. The project was called “cassakero”. The cassakero project aims to install 10,000 units of small-scale bio-ethanol refineries, operated by small-scale agro-processors across the country. The aim of this article is to present the results of an energy analysis of the ethanol cooking fuel produced from cassava feedstock by small-scale processors under Nigerian conditions Results show that for small-scale cassava ethanol production with the use of agrochemicals is: 11.61 MJ/l for total energy input, a Net Energy Ratio of 1.20, 2.29 MJ/l for Net Energy Gain, and 11.01 MJ/l for Net Renewable Energy Value. Without the use of agrochemicals ethanol production is 10.38 MJ/l for total energy input, a Net Energy Ratio of 1. 34, 3.52 MJ/l for Net Energy Gain, and 12.25 MJ/l for Net Renewable Energy Value. This is the first time that energy analysis has been carried out for small-scale cassava ethanol production under Nigerian conditions. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>